2019
DOI: 10.1155/2019/6450281
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Visit-to-Visit Variability of Blood Pressure Measured as Part of Routine Clinical Care among Patients Attending Cardiology Outpatient Department of a Tertiary Care Centre in Northern Sri Lanka

Abstract: Visit-to-visit variability (VVV) is a relatively new concept in the hypertensive arena. Data regarding VVV are lacking in our region, and factors associated with VVV are rarely examined in previous studies. This study was conducted among 406 patients attended to the cardiology outpatient department of Teaching Hospital, Jaffna, Sri Lanka, in 2018 to assess the long-term variability of blood pressure (BP) by reviewing last six consecutive BP readings from the records retrospectively. Data regarding sociodemogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Hypertension and diabetes usually co-exist, and diabetes independently contributes to the development of atherosclerosis, but hypertension increases the incidence and progression of cardiovascular events [17]. Diabetes has also been significantly associated with visit-to-visit variability in blood pressure measurements [18]. Many diabetic guidelines recommend SBP and DBP targets below 140 and 90 mm Hg, respectively, but below 130 and 80 mm Hg when significant proteinuria exists [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension and diabetes usually co-exist, and diabetes independently contributes to the development of atherosclerosis, but hypertension increases the incidence and progression of cardiovascular events [17]. Diabetes has also been significantly associated with visit-to-visit variability in blood pressure measurements [18]. Many diabetic guidelines recommend SBP and DBP targets below 140 and 90 mm Hg, respectively, but below 130 and 80 mm Hg when significant proteinuria exists [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Kumanan T et al, in their one-year study of longterm blood pressure variability of 406 patients, found that female sex (p=0.023), DM (p=0.013), CKD (p=0.007), and the tendency for developing OSA (p=0.004) were associated with significant variability. 9 A median value of 11.69 differentiated low and high variability groups. In multivariate analysis, only DM and CKD were significantly associated with high variability.…”
Section: Blood Pressure Variability As a Prognostic Markermentioning
confidence: 97%
“…In ARV, the sum of differences between successive BP measurements is divided by the number of total readings minus one and has been shown to provide the best estimate of BPV. 9 The therapeutic impact of BPV is yet to be established. However, certain studies have shown that Calcium channel blockers decrease, whereas beta-blockers and diuretics are inferior in this regards.…”
Section: Introductionmentioning
confidence: 99%
“…cardiovascular illnesses). [43][44][45][46] This method can be applied broadly wherever there is ongoing monitoring of a biological index that is closely dependent on patient behavior (e.g. blood pressure monitoring).…”
Section: Generalizabilitymentioning
confidence: 99%